Islamic bank margins in Indonesia: The role of market power and bank-specific variables - Agus Widarjono; Priyonggo Suseno; Devi Utami Rika Safitri; Atif Yaseen; Kurniawan Azra; Irma Nur Hidayah (Cogent Business & Management, 2023)
Our study examines the determinants of bank margins in Indonesian Islamic banks. The determinants of bank margins consist of market-and-bank-specific variables. We investigate 31 banks, using quarterly data from 2015: Q1 to 2020: Q4. Panel regression with unbalanced data is employed. The findings indicate that higher Islamic bank margins are positively linked to banks with higher market power. Bank with high risk-sharing financing has low bank margins. Bank-specific variables such as income diversification, risk-averse, financing, and financing risk influence bank margins. This study also documents that the effect of market power on Islamic bank margins is more pronounced in Islamic bank subsidiaries, and lower bank margins through risk-sharing financing are more prominent in Islamic bank subsidiaries. These results suggest important policy implications that Islamic banks should focus on risk-sharing financing as a core business of Islamic banks because it can reduce the price of Islamic bank financing products as well as their intermediation costs.
Keywords: G21; G32; 650; Indonesia; Islamic bank margins; Market power; risk-sharing financing